Naturally Occurring Calanolides: Occurrence, Biosynthesis, and Pharmacological Properties Including Therapeutic Potential - Nahar, Lutfun; Talukdar, Anupam Das; Nath, Deepa; Nath, Sushmita; Mehan, Aman; Ismail, Fyaz M D; Sarker, Satyajit D (Molecules (Basel, Switzerland), 2020)
Calanolides are tetracyclic 4-substituted dipyranocoumarins. Calanolide A, isolated from the leaves and twigs of Calophyllum lanigerum var. austrocoriaceum (Whitmore) P. F. Stevens, is the first member of this group of compounds with anti-HIV-1 activity mediated by reverse transcriptase inhibition. Calanolides are classified pharmacologically as non-nucleoside reverse transcriptase inhibitors (NNRTI). There are at least 15 naturally occurring calanolides distributed mainly within the genus Calophyllum, but some of them are also present in the genus Clausena. Besides significant anti-HIV properties, which have been exploited towards potential development of new NNRTIs for anti-HIV therapy, calanolides have also been found to possess anticancer, antimicrobial and antiparasitic potential. This review article provides a comprehensive update on all aspects of naturally occurring calanolides, including their chemistry, natural occurrence, biosynthesis, pharmacological and toxicological aspects including mechanism of action and structure activity relationships, pharmacokinetics, therapeutic potentials and available patents.
Keywords: calanolide A; anti-HIV; pseudocalanolides; Biological Products; lidé; Calophyllaceae; Calophyllum; Pyranocoumarins; reverse transcriptase; Humans; pyranokumariny; non-nucleoside reverse transcriptase inhibitors (NNRTIs); biologické přípravky; calanolides